2010
DOI: 10.1007/s00221-010-2476-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical delay but not subjective delay determines learning rate in prism adaptation

Abstract: Timing is critical in determining the causal relationship between two events. Motor adaptation relies on the timing of actions and their results for determining which preceding control signals were responsible for subsequent error in the resulting movements. An artificially induced temporal delay in error feedback as short as 50 ms has been found to slow the learning rate of prism adaptation. Recent studies have demonstrated that our sense of simultaneity is flexibly adaptive when a persistent delay is inserte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 66 publications
8
57
2
Order By: Relevance
“…The high velocities and short durations of articulatory speech movements, together with the fact that even the production of a simple CVC word requires sequential actions within and across articulators, may be the critical reason why even short delays in auditory feedback have such a detrimental effect on speech auditory-motor learning whereas comparable visual feedback delays have limited effects on visuo-motor learning in the case of slower and discrete reaching movements [14,15,16]. In our experimental task, vowel durations across all conditions were on average only ~185 ms in duration (and note that this acoustic vowel duration spans across both the oral opening and closing movements, with kinematic measures of each component separately often indicating durations as short as ~75–180 ms [21]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high velocities and short durations of articulatory speech movements, together with the fact that even the production of a simple CVC word requires sequential actions within and across articulators, may be the critical reason why even short delays in auditory feedback have such a detrimental effect on speech auditory-motor learning whereas comparable visual feedback delays have limited effects on visuo-motor learning in the case of slower and discrete reaching movements [14,15,16]. In our experimental task, vowel durations across all conditions were on average only ~185 ms in duration (and note that this acoustic vowel duration spans across both the oral opening and closing movements, with kinematic measures of each component separately often indicating durations as short as ~75–180 ms [21]).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, motor learning for the upper limb seems rather robust to such feedback delays. Although the initial rate of adaptation (and thus the coefficients of a learning function) may be affected more substantially, the extent of visuo-motor adaptation and initial after-effect (relative to a control condition with no additional delay beyond that inherently present in the feedback display system, which by itself can be as large as 60 ms [14]) may be either essentially unchanged [15] or reduced by ~35% [16] with a feedback delay of 100 ms, reduced by ~20% with a delay of 200 ms [14,16], and reduced by ~60%- with a delay of 5000 ms [16] (note that in all these studies visual feedback was blocked during the movement, with only feedback about final hand position provided with or without delay after completion of the movement; thus the true delays relative to movement execution were even larger than reported).…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (1960) investigated the effects of delayed visual feedback on a number of simple visual–motor tasks such as writing, drawing, and star- or maze-tracing tasks, and reported that performance, especially that for non-writing tasks, was greatly impaired under delayed visual feedback. Other studies also found that delayed visual feedback impairs other tasks such as steering (e.g., Smith and Sussman, 1970) and manual tracking (e.g., Miall et al, 1985), and reduces the rate and amount of prism adaptation (Kitazawa et al, 1995; Tanaka et al, 2011). …”
Section: Introductionmentioning
confidence: 95%
“…While performing an action, information on the timing of the sensory feedback has a crucial role in detecting the causal link between the action and its consequence (Kitazawa et al, 1995; Blakemore et al, 1999; Farrer et al, 2008; Tanaka et al, 2011; Honda et al, 2012a,b). For example, when the visual feedback is delayed, a self-generated visual motion is perceived as generated by someone else (Blakemore et al, 1999; Farrer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%